The role of the values format in the formation of the political community - سردار قادر محى الدين; مهدي أبوبكر حمةعلي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
It is accepting that human beings naturally seek for something that have intrest for them in their life, whether these things are materials or morals. This indicates that the individuals always looking for their interests and ambitions within the social community. These individuals constantly exchange their benefits and interests with others. Moreover, the political community, as the most prestigious entity, always struggle to preserve the individual interests within its community. It is generally accepting that this type of entity does not come from out the globe, yet the participation of individuals within this entity forms a strong pattern of ethics that reproduce the customs and traditions of society and then present its objectives and aspirations. The political power seeks to organize politics to protect this format so as to preserve the life of people in both socially and politically. This can be described as the value system that gathers the individuals in the political community around the common interests. This concept has a symbolic nature that includes the moral and ethical aspects which can be seen as essential parts of establishing both the law and political system.